Porous metallic MoO2-supported MoS2 nanosheets for enhanced electrocatalytic activity in the hydrogen evolution reaction1. Issue 12 (28th March 2015) - Yang, Linjing; Zhou, Weijia; Hou, Dongman; Zhou, Kai; Li, Guoqiang; Tang, Zhenghua; Li, Ligui; Chen, Shaowei
<x xml:space="preserve">Abstract</x> Porous metallic MoO2-supported MoS2 nanosheets exhibit excellent electrocatalytic activity for HER and robust electrochemical durability.